Sodium Fluctuations in Astroglia and Their Potential Impact on Astrocyte Function - Felix, Lisa; Delekate, Andrea; Petzold, Gabor C.; Rose, Christine R. (Frontiers in Physiology, 2020)
Astrocytes are the main cell type responsible for the regulation of brain homeostasis, including the maintenance of ion gradients and neurotransmitter clearance. These processes are tightly coupled to changes in the intracellular sodium (Na+) concentration. While activation of the sodium-potassium-ATPase (NKA) in response to an elevation of extracellular K+ may decrease intracellular Na+, the cotransport of transmitters, such as glutamate, together with Na+ results in an increase in astrocytic Na+. This increase in intracellular Na+ can modulate, for instance, metabolic downstream pathways. Thereby, astrocytes are capable to react on a fast time scale to surrounding neuronal activity via intracellular Na+ fluctuations and adjust energy production to the demand of their environment. Beside the well-documented conventional roles of Na+ signaling mainly mediated through changes in its electrochemical gradient, several recent studies have identified more atypical roles for Na+, including protein interactions leading to changes in their biochemical activity or Na+-dependent regulation of gene expression. In this review, we will address both the conventional as well as the atypical functions of astrocytic Na+ signaling, presenting the role of transporters and channels involved and their implications for physiological processes in the central nervous system (CNS). We will also discuss how these important functions are affected under pathological conditions, including stroke and migraine. We postulate that Na+ is an essential player not only in the maintenance of homeostatic processes but also as a messenger for the fast communication between neurons and astrocytes, adjusting the functional properties of various cellular interaction partners to the needs of the surrounding network.